Dampak E-commerce terhadap Munculnya Kreativitas Berwirausaha dan Daya Saing Usaha Mikro Kecil Muslimah Majelis Taqorrub Ilallah (MTI) Bekasi - Aris Fatoni; Iwan Setyawan; Idam Pirmansyah (Universitas Batanghari Jambi, 2023)
This study aims to determine the direct impact of e-commerce on entrepreneurial creativity and business competitiveness and to determine the indirect impact of e-commerce on competitiveness through moderating variables of entrepreneurial creativity. The sample is 50 people with the sampling technique using the simple random sampling method. This study uses primary data that is processed using Partial Least Square (PLS). The results of this study conclude that e-commerce directly affects entrepreneurial creativity, but e-commerce does not directly affect business competitiveness. Then entrepreneurial creativity directly affects competitiveness and through moderating variables of entrepreneurial creativity, e-commerce indirectly affects business competitiveness.